2002
DOI: 10.2337/diabetes.51.2007.s368
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea Stimulation of Insulin Secretion

Abstract: Sulfonylureas are widely used to treat type 2 diabetes because they stimulate insulin secretion from pancreatic ␤-cells. They primarily act by binding to the SUR subunit of the ATP-sensitive potassium (K ATP ) channel and inducing channel closure. However, the channel is still able to open to a limited extent when the drug is bound, so that high-affinity sulfonylurea inhibition is not complete, even at saturating drug concentrations. K ATP channels are also found in cardiac, skeletal, and smooth muscle, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
290
0
17

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(325 citation statements)
references
References 54 publications
(54 reference statements)
11
290
0
17
Order By: Relevance
“…Accordingly, the remaining part of the LA-induced stimulatory effect completely disappeared when the islets were challenged for 30 min with LA prior to the 48-hour antisense exposure period. The fact that a tolbutamide-induced insulin release (Proks et al 2002) was unaffected by both antisense oligonucleotide and LA indicates that the suppressive effect was specific.…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, the remaining part of the LA-induced stimulatory effect completely disappeared when the islets were challenged for 30 min with LA prior to the 48-hour antisense exposure period. The fact that a tolbutamide-induced insulin release (Proks et al 2002) was unaffected by both antisense oligonucleotide and LA indicates that the suppressive effect was specific.…”
Section: Discussionmentioning
confidence: 96%
“…Their hypoglycaemic action is attributed to a stimulation of insulin release that rapidly follows the drug's binding to a surface membrane receptor and a subsequent rise in cytoplasmic free calcium concentration [28,29]. We recently reported that glibenclamide, a second-generation sulfonylurea, also exerts a stimulatory effect on insulin synthesis when present over a prolonged period, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] ). We used constant infusion of a low dose of drug to achieve sustained occupancy of only high-affinity receptors.…”
Section: Glibenclamide Treatment In Mce Modelmentioning
confidence: 99%